Rethinking Islamic communication studies within UIN Mataram’s Horizon of Knowledge paradigm: A critical-integrative review - Andri Kurniawan; Mohammad Alawi; Lalu Ahmad Zaenuri; S. Salahudin; Nurhaidah Nurhaidah; Hamzan Azhari (Islamic Communication Journal, 2026)
The discourse on the integration of knowledge in Islamic Higher Education Institutions today often remains at the level of institutional and symbolic slogans, thus requiring critical philosophical and methodological examination. This study seeks to reread the position of Islamic communication within the Horizon of Knowledge paradigm of UIN Mataram by examining how this paradigm can serve as a foundation for the construction of integrative knowledge. Using a qualitative approach through library research and conceptual analysis, this study examines the integration of knowledge, Horizon of Knowledge, and the philosophy of Islamic communication studies through a critical-hermeneutic perspective. The findings indicate that Horizon of Knowledge is not merely an institutional identity but also a scientific paradigm grounded in integration, interconnection, and internalization, which positions revelation, reason, empirical experience, Islamic tradition, and modern theory within an integrated framework. Within this paradigm, Islamic communication studies are not understood merely in a normative sense within the dimension of da‘wah, but rather as an academic discipline with strong ontological, epistemological, axiological, and methodological foundations. This study concludes that Horizon of Knowledge offers a prophetic-integrative framework for the development of Islamic communication studies that is scientific, ethical, and transformative. ***** Diskursus integrasi ilmu di Perguruan Tinggi Keislaman hari ini sering kali berhenti sebagai slogan kelembagaan, simbolik, yang memerlukan tinjauan kritis secara filosofis dan metodologis. Penelitian ini hendak membaca ulang posisi komunikasi Islam dalam paradigma Horizon Ilmu UIN Mataram dengan menelaah bagaimana paradigma ini dapat menjadi dasar konstruksi ilmu yang integratif. Melalui pendekatan kualitatif dengan studi kepustakaan dan analisis konseptual, penelitian ini hendak mengkaji integrasi ilmu, Horizon Ilmu, dan falsafah ilmu komunikasi Islam secara hermeneutika-kritis. Hasil penelitian menunjukkan bahwa Horizon Ilmu tidak hanya menjadi identitas kelembagaan, melainkan sebagai paradigma keilmuan berbasis integrasi, interkoneksi, dan internalisasi yang menempatkan wahyu, akal, pengalaman empiris, tradisi Islam, dan teori modern. Dalam paradigma ini, ilmu komunikasi Islam tidak dipahami secara normatif dalam dimensi da’wah, namun menjadi disiplin ilmu dengan fondasi ontologis, epistemologis, aksiologis, dan metodologis yang kuat. Penelitian ini menyimpulkan bahwa Horizon Ilmu menawarkan kerangka profetik-integratif bagi pengembangan ilmu komunikasi Islam yang ilmiah, etis, dan transformatif.